Evaluation of banana germplasm and genetic analysis of an F 1 population for resistance to Fusarium oxysporum f. sp. cubense race 1 - Arinaitwe, I.K.; Teo, C.H.; Kayat, F.; Tumuhimbise, Robooni; Uwimana, Brigitte; Kubiriba, Jerome; Swennen, Rony L.; Harikrishna, J.A.; Othman, R.Y (Springer, 2019)
Fusarium wilt of bananas (Musa spp.), caused by Fusarium oxysporum f. sp. cubense (Foc) causes up to 100% yield loss in bananas. Foc race 1 in particular is very devastating to dessert bananas in Uganda. One of the effective control strategies for the disease is the development of resistant cultivars through breeding. The objectives of this study were to identify suitable banana germplasm for generating a segregating population for resistance to Foc race 1 and understand the mode of inheritance of resistance to Foc race 1. Twenty-two banana accessions sourced from the National Agricultural Research Organisation in Uganda were challenged with Foc race 1 in a screen house experiment. Monyet, resistant to Foc race 1 and Kokopo, susceptible, were selected and crossed to generate 142 F1 genotypes. These F1 genotypes were also challenged with Foc race 1 in a screen house experiment. Data were collected on rhizome discoloration index (RDI), leaf symptom index (LSI) and pseudo-stem splitting (PSS), and analysed for variability. The banana accessions evaluated showed varying degrees of resistance to Foc race 1. Segregation ratios for resistant versus susceptible progenies fitted 13:3 (χ2 = 0.12, P = 0.73) for RDI and 11:5 (χ2 = 3.04, P = 0.08) for PSS. Estimated broad sense heritability was 27.8% for RDI, 13.9% for LSI and 14.7% for PSS. The results suggest that resistance to Foc race 1 in banana is controlled by at least two dominant genes with epistatic interaction and that heritability of resistance to Foc race 1 is low in Musa spp.